Epidemiology of Pysichiatric Disorders (Texas Journal of Medical Science, 2022)
This article presents the epidemiology of mental disorder of several diseases such as anxiety disorders, schizophrenia, depression, bipolar disorder, post-traumatic stress disorder, eating disorders, destructive behavior and dissocial disorders and disorders of the nervous system development. The number of these diseases is shown